DFT study on the water-assisted mechanism for the reaction between VO+ and NH3 to yield VNH+ and H2O - Gracia, L.; Andres, J.; Beltran, A.; Sambrano, J. R. (Elsevier B.V., 2006)
On the basis of DFT calculations, an understanding on the catalytic effect of water in the dehydration reaction between VO+ and NH3 to yield VNH+ and H2O has been obtained. The Gibbs free energy profiles point out that the global process involves two consecutive hydrogen shifts from the nitrogen to the oxygen atom. The catalytic role is achieved by a water assisted mechanism in which water acts as proton donor and acceptor, via transition structures corresponding to a six-membered rings. The corresponding stationary points lie below both the entrance VO+ + NH3, and VNH+ + H2O, channels. (c) 2006 Elsevier B... All rights reserved.